Pathological characterization of lung lesions and molecular detection of Mycoplasma spp. in slaughtered goats - Vishnubashini , I; Priyadharshini , R; Praveen K; Poobitha S; Uma, S; Srinivas, MV; Lakkawar, AW; Raja, K (Journal of the Hellenic Veterinary Medical Society, 2025)
Mycoplasmosis is a chronic respiratory disease of goat causing huge economic loss to the farmers. A slaughter house based study was carried out from December 2023 to March2024 to characterize the gross, histopathological lesions in lungs and also to confirm the role of Mycoplasma spp. by PCR in slaughtered goats in Puducherry, India. Out of 350 carcasses examined, pneumonic lesions were recorded in 104 cases accounting for 29.7 %. All the affected animals in the present study were above 1 year of age. Sex wise lesions were recorded more in males (60.5%, 63/104) than females (39.4% 41/104). Breed wise, the occurrence of lung lesions were: salem black (28.8%, 30/104), kodiaadu (26.9%, 28/104) and non-descript (44.2%, 46/104). Gross examination revealed emphysematous, edematous and grey to red areas of consolidation with exudation from the cut surface. Representative tissue samples were collected and fixed in 10% formalin and processed by routine paraffin embedding techniques. Histopathological examination of affected lung tissue showed extensive area of haemorrhage, pleural thickening, bronchus associated lymphoid tissue [BALT] hyperplasia, septal thickening, epithelial hyperplasia and mononuclear infiltration. From histopathologically confirmed pneumonic cases, 6 samples were subjected to PCR targeting the 16srRNA specific for Mycoplasma spp. Out of 6 cases, four samples yielded an expected amplicon size of 450 bp (66.66%) confirming the involvement of Mycoplasma spp.